Psycholinguistic Mechanisms for Actualization of Translating Activities of the Interpreter - Ернест Івашкевич; Алла Яцюрик (Психолінгвістика, 2020)
The purpose of the article is to propose and justify the definition of “translation consciousness” of the interpreter.